What did it mean when knowledgeable Hopi called the moon Chief Qahopi? - McCluskey, Stephen C. (2024)
This study uses the methodology of the history of scientific ideas to critically examine several aspects of an unpublished ethnographic discussion in which Alexander Stephen describes nineteenth-century Hopi understandings of the Moon. As is common in the interpretation of early texts, we draw insights into a text's meaning from other writings by the author and his contemporaries.The Moon Chief is a man—& is so called (Müriyawû Moñwi) but does not seem to be held in much veneration, in fact they say he is Kaho’pi = foolish. He has no house– although like the Sun, he carries the Moon on his arm, shield fashion; during his journey [across the sky].Alexander M. Stephen, (1891-84, 18 Jan. 1894)Here we draw especially on the ethnographic writings of Alexander Stephen to shed light on how he interpreted Hopi astronomical conceptions of the Sun and the Moon and how he understood the terms Moon Chief and qahopi.First, we ask what kind of being did Stephen and his knowledgeable Hopi mean when they spoke of the Moon Chief? Next, we ask what does the word qahopi mean or, to use specific examples, what did a Hopi mean when they said that a man or a woman or the Moon Chief or a kind of behavior was qahopi? After having clarified the general meaning of qahopi and identified the nature of the Moon Chief as a spiritual being who carried the Moon across the sky, we ask what aspects of the Moon Chief 's behavior did Stephen's Hopi experts consider to be qahopi? We then ask how, or whether, the qahopi aspects of the Moon Chief 's behavior influenced the form of the Hopi's successful luni-solar calendar. Finally, what light does the fact that some knowledgeable Hopi considered the Moon Chief to lack a house and therefore to be qahopi shed on our understandings of Hopi astronomy and of the astronomy of the Hopi's protohistoric Pueblo predecessors?In this final section we draw on early studies of astronomies in prehistoric cultures to shed light on the astronomical concepts – principally the lunar standstills – that illuminate the Moon’s lack of a house in Hopi astronomy.